PEMULIHAN BERENANG LAMBAT GAYA BEBAS LEBIH EFEKTIF DIBANDINGKAN DENGAN PEMULIHAN BERENANG LAMBAT GAYA DADA DALAM MEMPERCEPAT PEMULIHAN DENYUT NADI SETELAH LATIHAN MAKSIMAL PADA ATLET RENANG PRIA GRUP RENANG BAYUSUTA DI DENPASAR - Wahyuni, Nila; Tirtayasa, Ketut; Purnawati, Susy (Sport and Fitness Journal; Volume 2, No.2, 2014, 2014)
The swimmer in Indonesia is still very difficult to compete with world athletes who constantly surge achievement. One reason is the lack of understanding of proper recovery methods or effective in supporting achievement that is slow swimming active recovery method. This study aims to prove the differences of effectiveness of slow frontcrawl swimming recovery with a slow breaststroke swimming recovery to accelerate pulse rate recovery of male Bayusuta swimmer group in Denpasar. Experimental research was done with the method of randomized pre and post test control group design, conducted on February 2014. Samples were selected by simple random sampling . The two intervention groups with each group of 17 samples that randomized selected. The first group was given intervention as slow frontcrawl swimming and the second groups given intervention as slow breaststroke swimming after maximal exercise 50 meter sprint swimming . Pulse rate recovery was measured using Brouha method that is  pulse rate in the first minute until the fifth minute. Statistical analysis with the Wilcoxon test showed a decrease in pulse rate in both groups from the first minute until the fifth minute showed a significant decrease (p < 0,05). Based on the Mann Whitney test pulse rate recovery in the first minute and the second showed no significant difference ( p > 0,05 ), while the third to fifth minute pulse recovery in both groups showed significant differences ( p < 0,05 ) . The decrease of pulse rate in both groups in the first minute until the fifth minute showed significant results ( p < 0,05 ). In conclusion is slow freestyle swimming recovery methods is more effective than  slow breaststroke swimming recovery method in accelerate swimmer pulse rate recovery. The results of this study are expected to increase the knowledge of coaches and swimmer to be able to do a proper recovery methods.
Keywords: Sport recovery, Frontcrawl swimming, Breaststroke swimming, Pulse rate